On the Sweet Fragrance of Healing in the Cult of Relics: Scented Oil Lamps, Holy myron and Myroblytes Saints - Lale Doğer; Ceylan Borstlap (Art-Sanat)
The fragrance, which emerged as an important element of the cult of saints, takes its place in religious rites in the Byzantine healing practices of sacred centers, funeral traditions and adventus ceremonies such as the consecration of an altar in the church. The physician-saints, who offer extraordinary therapeutic prescriptions with ordinary organic substances, play a major role in the relationship between relics and scent. As a source of miraculous healing, the saints have provided health services in the centers that have become hagios topos in the Byzantium geography since the Early Byzantine Period. The heavenly treatment was realized by anointing with holy waters agiasmós (ayazma) or rubbing by sacred blessings such as myron (μύρον), balsam, hnānā, soil and ointments; staying overnight in the sanctuaries for incubation and methods such as apomyrizo (ἀπομυρίζω) have been applied. The article evaluates with eulogia the cult-related elements, the phenomenon of smelling the therapeutic relics and finding healing with its spreading scent has been studied. The descriptions of the scented oils have been investigated in the miracle collections (martyrologium) handled through the Greek terminology of the Late Roman-Byzantine Period; by extension, the reliquaries used for scented relics and the oil lamps used as a part of a cult in the religious architecture has been examined. The word myron, which means ‘fragrant ointment’, has been etymologically studied in scriptures and hagiographic texts; was aimed to clarify the myroblytes (μυροβλύτης) saints, the meaning, and the Turkish translations of the word myron. According to the functions of scent, the classification of holy oils based on their time-spatial properties and the iconography of the fragrance have been defined.